Benefit of Working from Home during Covid-19: A Case of Kathmandu Valley - Upreti, Kalawati (Nepalese Journal of Business, 2024)
This study examines the benefit of working from home during covid-19 in Kathmandu Valley. The dependent variable is employee performance. The selected independent variables are out come on work domain, quality of work life, organizational culture, individual factors and family factor. The primary sources of data are used to assess the opinions of respondents regarding out come on work domain, quality of work life, organizational culture, individual factor and family factor. The study is based on primary data of 123 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of benefit of working from home during covid-19: A case of Kathmandu Valley. The study showed a positive impact of employee performance. It indicates that increasing in outcome of work domain leads to change in employee performance. Likewise, quality of work life is positively correlate to employee performance. It indicates that better quality of work life stimulates the employee performance. Similarly, organizational culture is positively correlated to employee performance. It indicates that better organizational culture can stimulate the employee performance. Further individual factor is also positively related to the employee performance. It indicates that individual factor leads to change in employee performance. Likewise, family factor is positively correlated to employee performance. It indicates that family factors leads to increase in employee performance.